Late-Onset Ictal Asystole and Falls Related to Severe Coronary Artery Stenosis: A Case Report - Fortunato, Francesco; Labate, Angelo; Trimboli, Michele; Spaccarotella, Carmen; Indolfi, Ciro; Gambardella, Antonio (Frontiers in Neurology, 2022)
Introduction: Ictal asystole (IA) is a rare, underestimated, and life-threatening cause of transient loss of consciousness and fall. Current treatment options for seizures associated with IA usually include cardiac pacemaker implantation. We report, for the first time, a case of IA that is related to coronary stenosis, which was resolved after coronary angioplasty. Case Presentation: A 73-year-old man had a 2-year history of focal seizures with impaired awareness. Three months before our observation, he started to have sudden falls resulting in injury on several occasions. General and neurological examinations, as well as brain MRI, were unremarkable. Interictal electroencephalography (EEG) showed bitemporal spiking. Ictal video-polygraphy revealed a diffuse electrodecrement, followed by a buildup of rhythmic 4–6 Hz sharp activity, which was more evident in the left temporal region. After the seizure onset, the ECG showed sinus bradycardia, followed by sinus arrest that was associated with the patient's fall from the standing position. Afterwards, sinus rhythm returned spontaneously. A diagnosis of IA was made. A comprehensive cardiologic evaluation revealed a sub-occlusive stenosis of the left anterior descending artery. Successful coronary angioplasty resolved IA, levetiracetam was added, and no seizure or fall has occurred in the following 20 months. Moreover, he underwent a 7-day Holter ECG monitoring, and no asystole was depicted. Conclusion: The present case was unique as it shows the potential association between IA and coronary stenosis, also suggesting a possible therapeutic role for coronary angioplasty. It also highlights the importance of carefully investigating epilepsy patients with falls, especially in the elderly, since IA-related falls can be easily misdiagnosed in older age. Thus, if IA is identified, a deeper cardiac evaluation should be considered. As seen in our patient, non-invasive diagnostic examination including routine, prolonged, and exercise ECG, as well as echocardiogram, were readily available and were informative in diagnosing cardiac abnormalities that are amenable to specific treatment.